Penerapan International Safety Management Code (ISM Code) Untuk Meningkatkan Keselamatan Awak Kapal Di Kapal MT. Palu Sipat - Ali Nurwijdan, Haidar; Antoro, Dwi; Hasmawati, Andi; A. Gani, Julita; Usabeny, Dewi (BINER : Jurnal Ilmu Komputer, Teknik dan Multimedia, 2025)
This research is based on the rise of UAUC (Unsafe Act Unsafe Condition) which triggers a threat to the safety of ship crews. This happened as a result of the negligent implementation of the ISM Code on board. The methods used are observation and interviews, so as to produce qualitative data which will then be transformed into useful information. Based on the results of observations and interviews, it is known that there are several factors that cause the low implementation of the ISM Code on board such as a lack of concern and an attitude that is indifferent to regulations and responsibilities towards the ISM Code. The implementation of the ISM Code can be done by checking the completeness and functions of pyrotechnic, SART, fire plan, fire hose box, SCBA as well as programs such as SIRE and periodic audits. The implementation of the ISM Code can be improved by means of training and education, the implementation of incentives for crew members who comply with ISM Code procedures, as well as toolbox activities and regular monthly safety meetings. Based on these findings, the researcher suggests that the ship and its crew increase awareness, understanding, and concern for the ISM Code so that they can avoid the possibility of bad things happening in the future and safety is more guaranteed.